Diseño de campañas comunitarias de educación sanitaria para la protección ambiental en las ecuelas de educación primaria del Valle de los Chillos - Rosero Vela, Alexander Patricio (2015)
The work is based primarily on an approach to theories about the environment and ecology before landing in environmental education and environmental education. These elements are basic to develop a community campaign, also known as social action campaigns, focusing on the issue of environmental education. To design the campaign a survey of perceptions of environmental children / school as teachers in schools and 31 May and Juan Montalvo, the Valley of the Chillos and Canton Rumiñahui subjects was performed. Additionally focus groups and interviews were conducted to supplement the survey data. The most important contributions of the campaign are designed to gain a better awareness of good environmental practices such as recycling and proper use of natural resources in school to acquire a better performance on environmental care.